Clinical Dilemmas: The Radiated Larynx. (2nd September 2014) - Merati, Albert L.; McWhorter, Andrew J.; Johns, Michael M.; Pryor, Jan; Allen, Clint T.
Abstract : Program Description: Airway, voice, and swallowing complaints following radiation present some of the most challenging clinical dilemmas in otolaryngology. This practice‐based minisemiar will bridge current scientific knowledge about radiation and its impact on the larynx with decades of clinical experience dealing with vocal fold lesions, vocal fold paralysis, airway obstruction, dysphagia, and chondroradionecrosis of the larynx. Succinct, highly focused presentations on these topics will aim for the shared objective of distilling key elements of clinical care issues that occur in the radiated larynx. Real‐life cases will be presented. Panelists are challenged to provide practical advice for the management of this patient population. Educational Objectives: (1) Explain the pathophysiology of laryngeal injury following radiation therapy, specifically as it relates to chondroradionecrosis. (2) Examine the limitations that prior radiation places on the otolaryngologist caring for patients with vocal fold lesions and paralysis. (3) Incorporate state‐of‐the‐art surgical and therapeutic options available for airway and swallowing rehabilitation in the radiated larynx.